559 IDENTIFYING PATIENTS WITH MOOD DISORDER FOLLOWING ADMISSION WITH HIP FRACTURE WITH A VIEW TO STARTING TREATMENT & PROVIDE ADVICE. (14th June 2021) - Giles, K; Hall, P; Wilson, H; Macpherson, L; Martin-Hernandez, M P; Thompson, K; Bailey, S
Abstract: Introduction: The signs of depression in the elderly often go unnoticed. The MDT at RSCH observed that low mood could negatively impact on patient's recovery, affecting pain thresholds and leading to poor engagement with rehabilitation. Proactive identification and management of mood disorder is an important part of CGA, but not routinely performed. The aim of this QI project is to improve identification and management of mood disorder in patients over 65 years admitted to RSCH with hip fractures by introducing a standardised assessment tool to guide appropriate interventions. Method: Notes of patients with hip fracture admitted over a four-month period were retrospectively reviewed to establish if patients were screened for low mood. A mood screening tool, Cornell Score, was chosen and implemented by OT's and junior doctors over a four-month period. Those identified with depression or probable depression were issued verbal advice, an information leaflet and follow-up arranged. Results: Ninety-eight patients were included in the retrospective cohort; There was no indication that mood was considered or assessed at any point during admission. During the four-month prospective period, 86 patients (96%) were screened for low mood; 9% had major depression and 16% probable depression. Feedback from our occupational therapists and doctors was positive, with the tool being easy to use in patients with or without cognitive impairment. Much of the assessment could be incorporated into initial assessment or in gaining collateral history. Anecdotally, considering patients psychological well-being had a positive impact on inpatient therapy sessions guided the MDT in supporting the patient appropriately. Conclusion: Implementation of a standardised and validated mood screening tool enabled us to identify that a quarter (25%) of the patients had, or probably had depression. This allowed us to intervene with simple measures such as verbal advice and an information leaflet and consider pharmacological intervention where appropriate.